2021
DOI: 10.3389/fpsyt.2021.680800
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision-Making and Role Preference Among Patients With Schizophrenia in Malaysia: A Cross-Sectional Study

Abstract: Introduction: Shared decision-making (SDM) is recognized as a promising strategy for improving collaboration between clinicians and their patients in achieving recovery. In Malaysia, SDM among people with schizophrenia is still lacking both in practice and in research. This study aimed to determine the level of SDM and role preference and their associated factors among patients with schizophrenia in Malaysia.Methods: A cross-sectional study was conducted on 86 outpatient attendees with schizophrenia at a teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…If Stereotype Endorsement and Alienation are a problem, then interventions such as NECT [ 48 ], Solution-focused Group Psychoeducation Program [ 49 ], Mindfulness-based Psychoeducation [ 44 ], or CBT-based psychoeducation program [ 47 ] that are known to effectively improve these targets may be utilized. Such tailored care may result in the following outcomes: an improved patient experience as a result of treatment decisions that take into account patients’ care needs and preferences; an improved population’s health and quality of life as a result of tailored care being supported; and a reduction in the per capita cost of care as a result of a reduction in the overuse, underuse, and misuse of healthcare services [ 68 ]. Furthermore, prior to implementing the intervention, it is essential to have a discussion about the options that are suitable and available, as well as the pros and cons of each, and to apply shared decision making between the patient and the doctor, as this may have many positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…If Stereotype Endorsement and Alienation are a problem, then interventions such as NECT [ 48 ], Solution-focused Group Psychoeducation Program [ 49 ], Mindfulness-based Psychoeducation [ 44 ], or CBT-based psychoeducation program [ 47 ] that are known to effectively improve these targets may be utilized. Such tailored care may result in the following outcomes: an improved patient experience as a result of treatment decisions that take into account patients’ care needs and preferences; an improved population’s health and quality of life as a result of tailored care being supported; and a reduction in the per capita cost of care as a result of a reduction in the overuse, underuse, and misuse of healthcare services [ 68 ]. Furthermore, prior to implementing the intervention, it is essential to have a discussion about the options that are suitable and available, as well as the pros and cons of each, and to apply shared decision making between the patient and the doctor, as this may have many positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration of structural elements is relevant for the current study because the "shared decision-making" dimension had the lowest factor loadings for the South Korean sample, as well as poor reliability. Shared decision-making involves healthcare professionals and patients working together on a care plan [28]. It entails patients who are willing to participate as well as clinicians who want to collaborate with the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Within Asian cultures, for example, it is more commonly believed that patients prefer to take a less independent role and that a family-centered (rather than individualcentered) approach towards decision-making is preferred [29][30][31]. It has been suggested that shared decisionmaking reflects values associated with western cultures and that this might be different in other cultures [28,31,32]. The value placed on shared decision-making and the structure of the healthcare system might therefore potentially impact the value of patient empowerment as perceived by study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Since SDM research was first initiated in Malaysian in 2010, there has been an increase in activity and focus on SDM. This is exemplified by a growing body of published studies on the subject and an increasing number of PDAs from Malaysia in fields as diverse as mental health [1] , [2] , primary care [3] , pharmaceutical consultations [4] , surgery [5] and genetics [6] . From a policy perspective, guidelines now emphasize in more detail how doctors are expected to communicate risks during consultations with patients [7] .…”
Section: Sdm In Malaysia- Growth In Research and Guidelinesmentioning
confidence: 99%